TEACHING ENGLISH TO YOUNG LEARNERS, EFFECTIVE STRATEGIES AND ACTIVITIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article presents an in-depth analysis of the most effective strategies for teaching English to young learners, based on both theoretical foundations and experimental teaching practices. It explores the psychological, linguistic, and pedagogical principles that influence language acquisition in children, highlighting the importance of developmentally appropriate methods such as Communicative Language Teaching (CLT), Total Physical Response (TPR), and the use of visuals and storytelling. The article underscores the significance of multisensory and interactive learning environments that align with the cognitive characteristics of young learners. An experimental lesson is described and analyzed, demonstrating how vocabulary acquisition, increased motivation, and active learner participation. The findings support the idea that teaching young learners requires creative, engaging, and learner-centered strategies that foster both language development and emotional wellbeing. Keyw